Meningkatkan Kemampuan Pemecahan Masalah Kalkulus Lanjut Melalui Pembelajaran Kooperatif Tipe Co-Op Co-Op - M Taufik Qurahman (Cakrawala: Jurnal Pendidikan, 2017)
In the learning process Diploma Study Program of Mechanical Engineering Polytechnic Harapan Bersama Tegal , it was found that there was lack of understanding of students in digesting the material issues related to advanced calculus, observation of the learning process only dominated by a model of learning lectures, discussion and administration tasks. As a result of this situation adversely affects the student problem-solving abilities. An appropriate mathematics learning model should be implemented to solve this problem. The research employed action research design and Cooperative - Cooperative (Co-op co-op) model to improve problem-solving abilities of students in the subject of advanced calculus, the purpose of this study was to determine whether the type of learning model Co-op co-op could improve problem-solving skills students of Diploma Study Program of Mechanical Engineering Polytechnic Harapan Bersama Tegal. There were 21 students who took advanced calculus courses. The learning media were course material unit, evaluation tools, observation sheet, and worksheet for group discussions. The research consisted of two cycles with the stages of planning, action, observation, and reflection. Both cycles used employed Co-op co-op learning model. And the results showed problem solving capability was increased significantly on advanced calculus course. There were 90.48% of 21 students received grades ≥70 in accordance with the specified minimum grades.